Biosentrisme dan Ekosentrisme: Alternatif Pandangan Filsafat Lingkungan terhadap Krisis Alam di Era Antroposentrisme: Biocentrism and Ecocentrism: Alternative Environmental Philosophical Views on the Crisis of Nature in the Era of Anthropocentrism - Priyono, Bagus Budi; Purwantara, Suhadi; Widyastuti, Widyastuti (Jurnal Filsafat Indonesia, 2025)
Global environmental crises, such as global warming, ecosystem degradation, and biodiversity loss, demonstrate the limitations of the anthropocentric approach that focuses on human interests in managing nature. As an alternative, biocentrism and ecocentrism offer a more inclusive view by emphasizing the intrinsic value of living things and the importance of maintaining the integrity of the ecosystem as a whole. This article uses a literature review method to explore the basic principles, differences, and relevance of these two approaches in dealing with the environmental crisis in the era of anthropocentrism. Through the identification, analysis, and synthesis of various current literatures, this article is expected to provide insight into how biocentrism and ecocentrism can contribute to more sustainable environmental policy updates. The results show that the implementation of biocentrism and ecocentrism views has been carried out in various countries. Indonesia, Bhutan, Costa Rica, and Nepal are some examples of countries that apply the biocentric view in formulating some of their policies. Ecuador, Australia, South Africa, and India are examples of countries that apply the ecocentric view in formulating some of their policies. This implementation replaces the anthropocentric view that has dominated environmental policy for centuries. This policy certainly supports the preservation, protection, and balance of the ecosystem.